MORPHOLOGICAL ANALYSIS OF METASTASES OF HEPAR WITH MR VOLUMETRY - Bozinovska, Biljana; Veljanova, Biljana Prgova; Janik, Violeta Hristova; Kostova, Masha; Veljanovski, Dimitar; Bogoevska, Andrea Nancheva; Jovanoska, Ivona (Journal of Morphological Sciences, 2025)
Increased frequency of incidence of metastatic liver disease has been noted especially among young women with breast cancer and young men with colorectal cancer. Metastatic liver deposits have a specific morphological appearance on MR . MR morphological imaging of metastases is based on proton spin of the hepatocytes, while the hepatic metastases have in a different sequence different display. On T1-sequence they are shown as focal hypo to isosignal round to oval irregular lesions of varying diameter sometimes with deeper central signal. The T2-sequence has a mixed signal depending on the type of vascularization, but specificity is obtained after intravenous application contrast, where metastases were shown with deep central signal but significant peripheral hypersignal in the form of a peripheral ring. Liver volumetry using magnetic resonance imaging (MRI) is method for quantitative measurement of the size and volume of the liver using MRI data. This is a non-invasive technique that provides important information about the anatomy of the liver and can help in the assessment of diseases and liver conditions, such as cirrhosis, liver tumors, metastases or fatty liver disease. In metastatic liver disease, hepatic volumetry as a method of calculating the residual the volume of the liver began to develop more and more with the development of the treatment of metastases, either surgical or oncological. The method represents a mathematical approach in date residual and responsible for the regenerative hepatic process, without affecting its function.  Magnetic resonance imaging and volumetry are superior methods for diagnosis and treatment of metastases. Keywords : MRI, Volumetry, Metastases, Liver.